Nitrogen doping for adhesion improvement of DLC film deposited on Si substrate by Filtered Cathodic Vacuum Arc (FCVA) technique - D. Bootkul (2018)
Diamond-like carbon (DLC) films have been used in many applications due to their attractive combination of properties including chemical inertness, corrosion protection, biocompatibility, high hardness, and low wear rates. However, they still have some limitations such as high internal stresses and low toughness which lead to poor adhesion of films. Synthesis of nitrogen-doped DLC (N-DLC) offers the possibility of overcoming these limitations. In this study, DLC films, namely tetrahedral amorphous carbon (ta-C) and nitrogen doped tetrahedral amorphous carbon (ta-C:N) were deposited on single crystalline Si wafer substrates using the Filtered Cathodic Vacuum Arc (FCVA) technique. Film characterizations were carried out by Raman spectroscopy, atomic force microscopy (AFM), scanning electron microscopy (SEM), triboindenter tester and nano-scratch tester. Measurement results showed that intentionally doping with nitrogen reduced the carbon sp3content and increased the surface roughness in comparison with that of pure ta-C films. The hardness measurement confirmed the Raman and AFM analyses that adding nitrogen in ta-C films decreased the hardness, especially with high nitrogen content. However, the nano-scratch test revealed the increasing of the critical load with nitrogen. This work, then, extended its scope to investigate the properties of double-layer ta-C films which were composed of ta-C:N interlayer of various thickness around 10-30 nm and ta-C top-layer with thickness of around 80 nm. Microstructure characterization demonstrated that a ta-C:N interlayer gradually decreased the sp3fraction in the films and increased film roughness whenever the ta-C:N interlayer thickness increased. In this structure, the tribological property in terms of adhesion to the Si substrate was significantly improved by about 20-90%, but the mechanical property in terms of hardness was gradually degraded by about 2-10%, compared to pure ta-C film, when the ta-C:N interlayer thickness increased from around 10-30 nm. This indicates that the nitrogen-doped DLC interlayer may sacrifice the mechanical strength of the films but gain benefits in terms of the adhesion property. © 2014 Elsevier B.V.